Is HIV Self-Testing a Strategy to Increase Repeat Testing Among Pregnant and Postpartum Women? A Pilot Mixed Methods Study. (1st August 2020) - Oyaro, Patrick; Kwena, Zachary; Bukusi, Elizabeth A.; Baeten, Jared M.
Abstract : Introduction: Repeat HIV testing among pregnant and postpartum women enables incident HIV infection identification for targeted interventions. We evaluated oral HIV self-testing (HIVST) for repeat HIV testing among pregnant and postpartum women attending busy public clinics in East Africa. Methods: Between October 2018 and January 2019, we conducted a pilot mixed methods study to evaluate the acceptability of oral-based HIVST among pregnant and postpartum women within 3 public health facilities in Kisumu County, Kenya. We invited 400 seronegative pregnant and postpartum women to choose between clinic-based oral HIVST and the standard finger prick provider-initiated testing and counseling for repeat HIV testing. We measured the frequency of each choice and described the participants' experiences with the choices, including data from 3 focus group discussions. Results: Slightly over half of the women [53.8%, 95% confidence interval (CI): 48.7 to 58.7] chose oral HIVST. Unmarried women were more likely to use HIVST (prevalence ratio: 1.26, 95% CI: 1.01 to 1.57, P < 0.05). The most frequent reason for oral HIVST selection was the fear of the needle prick (101/215, 47.0%). More HIVST than provider-initiated testing and counseling users indicated lack of pain (99.1% vs 34.6%, P < 0.001) and the need for assistance (18.1% vs 1.1%, P < 0.001) as reflective of their HIV testing experiences. Participants choosing HIVST cited privacy, ease, and speed of the procedure as the main reasons for their preference. Conclusions: The use of HIVST in Kenyan antenatal and postpartum settings seems to be feasible and acceptable for repeat HIV testing. Future work should explore the practical mechanisms for implementing such a strategy.